2019
DOI: 10.1002/epi4.12345
|View full text |Cite
|
Sign up to set email alerts
|

Practice trends and the outcome of neuromodulation therapies in epilepsy: A single‐center study

Abstract: Neuromodulation therapies (VNS, RNS, and DBS) can improve seizure control in persons with epilepsy. However, there is a significant service gap in integrating these therapies in clinical care. Our epilepsy center has established an epilepsy neuromodulation clinic to improve access to patients, communication with referring physicians, track outcome and train future providers in programming neuromodulation devices. We report the (a) treatment outcome of the available neuromodulation therapies (ie, reduction in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…A single RCT study (with two linked publications; see Supplementary Materials Table 1) was excluded due to unclear reporting of the enrolled population (i.e., proportion of adults) [48,49]. A total of 12 adult comparative observational study publications were excluded for the following reasons: no comparator (n = 4) [50][51][52][53], population of interest (n = 2) [54,55], reported no outcomes of interest (n = 5) [56][57][58][59][60] and superseded by a linked primary publication (n = 1) [61].…”
Section: Rcts and Comparative Observational Studiesmentioning
confidence: 99%
“…A single RCT study (with two linked publications; see Supplementary Materials Table 1) was excluded due to unclear reporting of the enrolled population (i.e., proportion of adults) [48,49]. A total of 12 adult comparative observational study publications were excluded for the following reasons: no comparator (n = 4) [50][51][52][53], population of interest (n = 2) [54,55], reported no outcomes of interest (n = 5) [56][57][58][59][60] and superseded by a linked primary publication (n = 1) [61].…”
Section: Rcts and Comparative Observational Studiesmentioning
confidence: 99%
“…As an adjunctive therapy, numerous studies have reported that VNS can effectively reduce seizure frequency 4 . After either two or three‐five years of stimulation, approximately 50% and 60% of epilepsy patients, respectively, were reported to achieve a ≥50% seizure reduction 5,6 . Commonly employed stimulation parameters are as follows: between 1.5 and 2.25 mA, 20‐30 Hz, 250‐500 μs, on time 30 s, off time 3‐5 min, which mainly based on doctors’ experience 7 .…”
Section: Introductionmentioning
confidence: 99%
“…proportion of adults) [48,49]. A total of 12 adult comparative observational study publications were excluded for the following reasons: no comparator (n=4) [50][51][52][53], population of interest (n=2) [54,55], reported no outcomes of interest (n=5) [56][57][58][59][60] and superseded by a linked primary publication (n=1) [61].…”
Section: Rcts and Comparative Observational Studiesmentioning
confidence: 99%